31.4k views
3 votes
-7(2b-4)=5(-2b+6)(if there is no solution,type in ''no solution'') b= Answer

User Natarsha
by
5.1k points

2 Answers

5 votes

Hope it will help u.............

-7(2b-4)=5(-2b+6)(if there is no solution,type in ''no solution'') b= Answer-example-1
User Barath Ravikumar
by
5.4k points
7 votes

Answer:

b = -2/4 or -0.5

Explanation:

- 7 (2b - 4) = 5 (-2b + 6)

-14b + 28 = -10b + 30

-14b + 10b = 30 - 28

-4b = 2

-b = 2/4

b = -2/4

-2/4 = -0.5

User Sachin Gaur
by
5.1k points